Research Progress in Natural Sources, Biosynthesis and Metabolism Regulation of Rutin in Plant-Derived Food Materials - ZHOU Ting, WANG Haige, ZHANG Jixing, BAO Yingcai, YU Yongli, CHANG Jie (Shipin Kexue)
Rutin, a flavanol glycoside derived from quercetin, is classified as a secondary metabolite from the phenylpropane metabolic pathway in higher plants. It possesses various pharmacological and physiological activities, including antioxidant, anti-aging, anti-inflammatory, anti-diabetic, and anti-cancer properties. With the deepening of pharmacological and physiological research on rutin, plant-derived foods rich in it have garnered significant research attention in the food industry. Biotransformation techniques, such as germination, have been shown to effectively enhance the rutin content and nutritional value of plant-derived foods by regulating the synthesis and metabolism of rutin in plants. This article summarizes the natural sources and biosynthesis pathways of rutin in plants as well as the characteristics and regulation of the key enzymes involved in rutin metabolism, hoping to provide a theoretical basis and research ideas for enriching rutin in plant-derived food materials and facilitating the development and application of functional and plant-based foods.